2022
DOI: 10.3389/fonc.2022.985281
|View full text |Cite
|
Sign up to set email alerts
|

Clinical prognosis of intraoperative blood salvage autotransfusion in liver transplantation for hepatocellular carcinoma: A systematic review and meta-analysis

Abstract: BackgroundIntraoperative blood salvage autotransfusion(IBSA) has been widely used in a variety of surgeries, but the use of IBSA in hepatocellular carcinoma (HCC) patients undergoing liver transplantation (LT) is controversial. Numerous studies have reported that IBSA used during LT for HCC is not associated with adverse oncologic outcomes. This systematic review and meta-analysis aims to estimate the clinical prognosis of IBSA for patients with H+CC undergoing LT.MethodsMEDLINE, Embase, Web of Science, and Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Furthermore, studies regarding its safety in hepatectomy for hepatocellular carcinoma, both retrospective and meta-analyses, have also been well-reported, such as recent works by Kwon and colleagues. [19][20][21][22][23][24] However, the comparative evidence specific to CRC is sparser. As discussed, several older studies have demonstrated viable circulating tumor cells (cTCs) in the peripheral blood of patients undergoing resection of CRLM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, studies regarding its safety in hepatectomy for hepatocellular carcinoma, both retrospective and meta-analyses, have also been well-reported, such as recent works by Kwon and colleagues. [19][20][21][22][23][24] However, the comparative evidence specific to CRC is sparser. As discussed, several older studies have demonstrated viable circulating tumor cells (cTCs) in the peripheral blood of patients undergoing resection of CRLM.…”
Section: Discussionmentioning
confidence: 99%
“…Large pan‐cancer meta‐analyses have generally reported on the safety of autotransfusion. Furthermore, studies regarding its safety in hepatectomy for hepatocellular carcinoma, both retrospective and meta‐analyses, have also been well‐reported, such as recent works by Kwon and colleagues 19–24 . However, the comparative evidence specific to CRC is sparser.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al performed a systematic review and meta-analysis of the literature published until May 1, 2022. 75 They identified 12 studies enrolling 2253 cases undergoing LT for HCC (1374 IAT and 879 non-IAT cases). The recurrence rate of HCC in the IAT group was slightly lower than that in the non-IAT group at 5 years (OR .75; 95% CI, .59-.95; P = .02) and 7 years (OR .65; 95% CI, .55-.97; P = .03).…”
Section: Liver Transplantationmentioning
confidence: 99%